White smoke - Jackson, Tiffany D. (Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2021)
Believing her new home to actually be alive, especially when her brother almost dies, Marigold and her new blended family won't be safe until she brings the truth to light once and for all.